İttifakın Bedeli: Birinci Dünya Savaşı’nda Osmanlı Kamuoyunda Rus Karadeniz Filosu Sorunu - Ahmet KÖKSAL (Gazi Akademik Bakış)
The fall of the Russian Navy into German hands by the Treaty of Brest-Litowsk also caused serious mobility in the Ottoman public opinion. As required by the law of the alliance, the Ottoman press suddenly began to include recurring news, such as the struggle of the Ottoman State in the Black Sea and the historical rivalry with the Russians in the harsh conditions of the war. This excitement soon increased expectations. Every day, a new article or editorial addressed this problem. The articles discussed at length that there was no doubt the Russian fleet was the spoils, while on the one hand, all the aspects of the issue, such as the historical process and the law of states, were evaluated. The newspaper articles explicitly dealt with the Black Sea issue, with particular emphasis on Germany and other allies to understand why the navy was so important to the Ottomans. Some open messages were also given to the government in order to do what was necessary due to external developments in the press, and it was stated that no information should be hidden from the Ottoman public.